Characterization of human UGT2A3 expression using a prepared specific antibody against UGT2A3. Issue 4 (August 2019) - Gotoh-Saito, Saki; Abe, Takayuki; Furukawa, Yoichi; Oda, Shingo; Yokoi, Tsuyoshi; Finel, Moshe; Hatakeyama, Masahiko; Fukami, Tatsuki; Nakajima, Miki
Abstract: UDP-Glucuronosyltransferase (UGT) 2A3 belongs to a UGT superfamily of phase II drug-metabolizing enzymes that catalyzes the glucuronidation of many endobiotics and xenobiotics. Previous studies have demonstrated that UGT2A3 is expressed in the human liver, small intestine, and kidney at the mRNA level; however, its protein expression has not been determined. Evaluation of the protein expression of UGT2A3 would be useful to determine its role at the tissue level. In this study, we prepared a specific antibody against human UGT2A3 and evaluated the relative expression of UGT2A3 in the human liver, small intestine, and kidney. Western blot analysis indicated that this antibody is specific to UGT2A3 because it did not cross-react with other human UGT isoforms or rodent UGTs. UGT2A3 expression in the human small intestine was higher than that in the liver and kidney. Via treatment with endoglycosidase, it was clearly demonstrated that UGT2A3 was N -glycosylated. UGT2A3 protein levels were significantly correlated with UGT2A3 mRNA levels in a panel of 28 human liver samples ( r  = 0.64, p  < 0.001). In conclusion, we successfully prepared a specific antibody against UGT2A3. This antibody would be useful to evaluate the physiological, pharmacological, and toxicological roles of UGT2A3 in human tissues. Graphical abstract: Image 1